Answer:
(3 – 6y²)(y² + 2) = - 6y⁴ - 9y² + 6
Explanation:
Given the expression
3-6y² and y²+2
We have to find the product of 3-6y² and y²+2
Clara's Solution:
(3 – 6y²)(y² + 2) = 3(y²) + (–6y²)(2)
= 3y² – 12y²
= -9y²
NO!
The student's work is INCORRECT!
Clara did not imply the correct distribution of multiplying the terms in the first step.
Here is the correct solution:
(3 – 6y²)(y² + 2) = 3(y²) + (–6y²)(2) + (3)(2) + (–6y²)(y²)
= 3y² – 12y² + 6 - 6y⁴
= - 6y⁴ - 9y² + 6
Therefore,
(3 – 6y²)(y² + 2) = - 6y⁴ - 9y² + 6